Rancangan VFR Route Yang Menghubungkan Bandar Udara Tjilik Riwut Menuju Bandar Udara Syamsudin Noor - Widodo; Hana Agita Mardiana; Lina Rosmayanti; Elvi Amir (Politeknik Penerbangan Indonesia Curug, 2021)
This study aims to find out the problems that occur related toflight a VFR from Palangkaraya towards Banjarmasin or otherwise fly direct result of the unavailability of VFR Route between tjilik riwut airport to airport Syamsudin Noor as well as the draft VFR Route as solutions to these problems. The research method used is level one research and development methods with data collection techniques in the form of interviews, literature studies and documentation studies. Data processing techniques use data reduction, data presentation, verification and use reference materials.